Chapter 19: Marketing Strategies for Vegetable Growers - John J. VanSickle (EDIS)
Developing an effective marketing strategy is an important key to success for vegetable growers. Like other businesses, vegetable growers must contend with many factors that are beyond their control. Reducing risk and managing uncertainty is how businesses and growers can improve profits. It is just as important for a grower to develop a marketing strategy as it is for a large corporation. This document is FRE144, Horticultural Sciences Department, UF/IFAS Extension. Published November 2006.